2018
DOI: 10.1186/s12885-018-4334-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin use on the risk and prognosis of endometrial cancer: a systematic review and meta-analysis

Abstract: BackgroundPrevious studies have suggested that metformin may be useful for preventing and treating endometrial cancer (EC), while the results have been inconsistent. This systematic review and meta-analysis aimed to investigate the association between metformin use and risk and prognosis of patients with EC.MethodsPubMed, Embase, and the Cochrane Library databases were searched for observational studies evaluating the effect of metformin on EC prevention or treatment. The odds ratio (OR) was used for analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 61 publications
2
56
0
Order By: Relevance
“…Epidemiological studies reveal that cancer-related mortality rate is significantly lower in metformin patient users and that survival rates is improved in many types of cancer patients, i.e., colorectal, pancreatic, breast, liver and endometrial cancers [ 106 , 107 ]. A recent study demonstrated that metformin significantly prolonged the OS (HR = 0.61; 95% CI = 0.48–0.77) and reduced recurrence risk (HR = 0.50; 95% CI = 0.28–0.92) in endometrial cancer [ 108 ]. Regarding endometrial cancer, results showed that metformin amplify the effects of paclitaxel by blocking mTOR-signalling pathway [ 109 ].…”
Section: Drug Repurposing For Ovarian Cancer Therapymentioning
confidence: 99%
“…Epidemiological studies reveal that cancer-related mortality rate is significantly lower in metformin patient users and that survival rates is improved in many types of cancer patients, i.e., colorectal, pancreatic, breast, liver and endometrial cancers [ 106 , 107 ]. A recent study demonstrated that metformin significantly prolonged the OS (HR = 0.61; 95% CI = 0.48–0.77) and reduced recurrence risk (HR = 0.50; 95% CI = 0.28–0.92) in endometrial cancer [ 108 ]. Regarding endometrial cancer, results showed that metformin amplify the effects of paclitaxel by blocking mTOR-signalling pathway [ 109 ].…”
Section: Drug Repurposing For Ovarian Cancer Therapymentioning
confidence: 99%
“…Randomised biomarker studies have so far failed to demonstrate a reduction in endometrial proliferation with 2–16 weeks of metformin treatment [ 38 , 39 ]. Similarly, metformin has not been shown to reduce endometrial cancer risk (OR 1.05, 95% CI 0.82–1.35, p = 0.7), but may improve risk of recurrence or overall survival [ 40 ].…”
Section: Prevention In the General Populationmentioning
confidence: 99%
“…Endometrial cancer (EC), mainly occurred in postmenopausal women, is one of the most common malignancies of the female reproductive system with the incidence of about 1/10,000 in worldwide [ 1 ]. EC is conventionally classified into type I (estrogen-dependent) EC and type II (estrogen-nondependent) EC according to molecular genetic features and clinicopathological features, and grades 1 and 2 are regarded as “type I”, while grade 3 is regarded as “type II” [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%